Online Advertising as Passive Search - Ursu, Raluca Mihaela; Simonov, Andrey; An, Eunkyung (Management Science, 2025)
Standard search models assume that consumers actively decide on the order, identity, and number of products they search. We document that online, a large fraction of searches happen in a more passive manner, with consumers merely reacting to online advertisements that do not allow them to choose the timing or the identity of products to which they will be exposed. Using a clickstream panel data set capturing full URL addresses of websites that consumers visit, we show how to detect whether a click is ad initiated. We then report that in the apparel category, ad-initiated clicks account for more than half of all website arrivals, are more concentrated early on in the consumer search process, and lead to less in-depth searches and fewer transactions, consistent with the passive nature of these searches. To account for these systematic differences between active and passive searches, we propose and estimate a simple model that accommodates both types of searches. Our results show that incorrectly treating all searches as active inflates the estimated value of brands that advertise frequently. Our model can more accurately recover data patterns, especially for advertising brands. We finish with model extensions and a discussion of the managerial implications. This paper was accepted by Dmitry Kuksov, marketing. Supplemental Material: The online appendix and data files are available at https://doi.org/10.1287/mnsc.2022.02154 .